1993
DOI: 10.1007/bf00126444
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and conformational analysis of the antiinflammatory agent amfenac and analogues

Abstract: The new nonsteroidal antiinflammatory drug (NSAID) arylacetic amfenac (2-amino-3-benzoylphenylacetic acid) and 19 substituted derivatives were studied in order to correlate the biological activities with the structure-related parameters. The geometry of amfenac in neutral and anionic form was totally optimized, starting from standard geometries and crystallographic data, using semiempirical AM1 and MNDO quantum-mechanical methods. Conformational analysis shows the existence of a rigid structure for rotations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…The higher the value, the better the penetration, with a 1.0-unit difference in the coefficient representing a tenfold difference in penetration. Ruiz et al 6 reported that the C log P of bromfenac (2.23) is higher than other NSAIDs, such as amfenac (1.23) and ketorolac (1.88). This difference in C log P explains the higher lipophilicity of bromfenac that provides a more rapid saturation of the epithelium and a minimal lag time before the drug crosses the cornea and, thus, the fast analgesic action.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The higher the value, the better the penetration, with a 1.0-unit difference in the coefficient representing a tenfold difference in penetration. Ruiz et al 6 reported that the C log P of bromfenac (2.23) is higher than other NSAIDs, such as amfenac (1.23) and ketorolac (1.88). This difference in C log P explains the higher lipophilicity of bromfenac that provides a more rapid saturation of the epithelium and a minimal lag time before the drug crosses the cornea and, thus, the fast analgesic action.…”
Section: Introductionmentioning
confidence: 97%
“…1 Preclinical data demonstrated that this halogenation of the molecule not only produced greater in vitro and in vivo potency, 2-5 but also enhanced bromfenac absorption across the cornea and penetration in ocular tissues. 6,7 The octanol/water (O/W) partition coefficient (C log P ) and the quantitative structure-activity relationship (QSAR) of a drug is another factor that influences its penetration properties and, consequently, its potency. C log P estimates the water solubility and the level of lipophilicity of a compound (a key determinant of the pharmacokinetics parameter).…”
Section: Introductionmentioning
confidence: 99%
“…20 Preclinical data demonstrate that halogenation of the bromfenac molecule increases in vitro and in vivo potency, improves absorption across the cornea, and enhances penetration through the ocular tissues. 21,22 In an in vitro inhibition analysis of IC 50 assays, bromfenac was found to be the most potent inhibitor of the COX-2 enzyme, ranging from 3 to 18 times more potent than the other available ophthalmic NSAIDs (amfenac, diclofenac, and ketorolac). 12,23 Bromfenac sodium ophthalmic solution 0.1% (Bronuck ® ; Senju Pharmaceutical Co., Ltd., Osaka, Japan) received regulatory approval in Japan in 2000 and is indicated for the treatment of ocular inflammatory diseases (blepharitis, conjunctivitis, and scleritis, including episcleritis) and postoperative inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism of action is believed to result from its potent (in the nM range) inhibitory effect on cyclooxygenase (COX)-1 and -2 and, thus, on prostaglandin synthesis [7,9]. The presence of bromine in the bromfenac molecule increases the lipophilicity of bromfenac, with the drug being more lipophilic than amfenac (another NSAID) [partition coefficient (log P) of 2.23 vs. 1.23] [10]. It also increases the drug's potency against COX-1 and COX-2 compared with amfenac [9].…”
Section: Introductionmentioning
confidence: 99%